2008
DOI: 10.22358/jafs/66683/2008
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes of serum leptin, insulin, IGF-I and thyroid hormones levels in growing Jinhua and Landrace gilts

Abstract: The present study was aimed to investigate the age-related changes of the serum IGF-I, leptin, insulin, triiodothyronine (T 3 ) and thyroxine (T 4 ) levels in pigs of different breeds. Jinhua and Landrace gilts were sampled at 35, 80 and 125 days of age, respectively. Serum hormone levels were measured with RIA. Serum IGF-I, leptin levels increased with age and displayed breed differences. Jinhua gilts showed lower (P<0.05) serum IGF-I and higher (P<0.05) leptin levels compared with Landrace gilts. In contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In our study, the mRNA levels of TRa in subcutaneous adipose tissue were associated with the fat percentage, Jinhua pigs had significantly lower TRa mRNA expression levels compared to Yorkshire pigs. Miao et al (2008) also found a negative relationship between serum thyroid hormone levels and carcass fat content of pigs. These results indicate that thyroid hormone and its receptor TRa may have a negative relationship with body adiposity in growing pigs, and subcutaneous fat expression of TRa may directly influence functions of adipocytes.…”
Section: Discussionmentioning
confidence: 76%
“…In our study, the mRNA levels of TRa in subcutaneous adipose tissue were associated with the fat percentage, Jinhua pigs had significantly lower TRa mRNA expression levels compared to Yorkshire pigs. Miao et al (2008) also found a negative relationship between serum thyroid hormone levels and carcass fat content of pigs. These results indicate that thyroid hormone and its receptor TRa may have a negative relationship with body adiposity in growing pigs, and subcutaneous fat expression of TRa may directly influence functions of adipocytes.…”
Section: Discussionmentioning
confidence: 76%